Interspecies interaction of Serratia plymuthica 4Rx13 and Bacillus subtilis B2g alters the emission of sodorifen. Issue 22 (11th October 2018) - Kai, Marco; Piechulla, Birgit
Abstract: Sodorifen is the major volatile of Serratia plymuthica 4Rx13. It is assumed to be a long-distance communication signal. However, so far the emission patterns of sodorifen had been studied using mono-cultures of S. plymuthica 4Rx13 neglecting that in natura bacteria live in communities. Here, we show that the structured co-cultivation of S. plymuthica 4Rx13 and Bacillus subtilis B2g in a low-diversity model community grown under nutrient-rich conditions led to quantitative changes in sodorifen emission compared to self-paired mono-cultivations. Co-culturing revealed a decreased emission of sodorifen (50%) during exponential growth phase, whereas in the late stationary stage of growth, the amount of headspace sodorifen was increased compared to self-paired mono-cultivation (217% at 500 h of cultivation). Six other compounds that are most probably related to sodorifen or are isomers showed similar emission patterns. These data indicated that S. plymuthica 4Rx13 enhances its communication signal sodorifen as a consequence of interaction with B. subtilis B2g. Abstract : Serratia plymuthica 4Rx13 enhances its communication signal sodorifen as a consequence of interaction with Bacillus subtilis B2g.